PROMOSI USAHA “FOODY DOLLYS” MENGGUNAKAN TEKNIK FOTOGRAFI UNTUK MENINGKATKAN PENJUALAN PRODUK - Cahyaning Umul Chasanah Nursyifani; Lutfi Tri Atmaji (Gestalt : Jurnal Desain Komunikasi Visual, 2019)
Photography is one aspect that producers need to consider in promoting their products. Photography can make an object, become more interesting and valuable. Today, buyers can see the product first without having to go to sales outlets. Photos become the main communication that connects producers and consumers in the sale of a product. This initial appearance is very influential in the purchasing decision process by consumers. Product appearance is important because product quality can only be judged by an image. New buyers can assess other aspects when a product has been purchased or come to a sales outlet. Therefore, photography on a product becomes very important to learn. Good photography techniques can increase the value of a product in order to compete with mass producers who have greater resources than them. Keywords: Photography, promotion, product